Les connaissances au quotidien : perceptions et savoirs des populations riveraines de l’Amazonie sur leurs ressources halieutiques - D. Sampaio da Silva; M. Lucotte; S. Paquet (Confins)
In this paper we are interested on subsistence fishing practiced by riparian Amazonian populations. The results presented, concerning the traditional knowledge of inhabitants, their perceptions about the environmental changes and the evolution of fishery resources as well as the some solutions regarding these changes, derived from two surveys administated to twelve communities of the Tapajós Basin. These results shed new light on issues related to the management of fisheries resources and highlight the gaps preventing a real appropriation of environmental problems and the emergence of local solutions. Indeed, we show that deforestation and erosion of river banks were perceived as the major environmental changes observed over the time. The decrease in abundance and/or reduction in the sizes of fish was also been reported by respondents. The lack of connection between the observed changes in natural ecosystems and changes in fish stocks caught our attention. Consequently, any intervention aimed at developing and/or implementing of methods for sustainable exploitation of fisheries resources must integrate preliminary activity information. The intention is to generate local ownership of environmental issues and encourage the emergence of solutions within the communities concerned.